KUALITAS DAN HARGA PRODUK MEMPENGARUHI KEPUTUSAN PEMBELIAN PAKAIAN MERK MANGO (STUDI KASUS PADA KARYAWATI KPMG SIDDHARTAWIDJAJA DAN REKAN) - Irma Selliamanik (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study is intended to examine the effect of mango brand product quality and price on buying interest in improving purchasing decisions. The sample of this study was 100 employees of KPMG Siddharta Widjaja and Rekan. This research was conducted using descriptive analysis method with a quantitative approach, data analysis using inferential statistics with multiple linear regression test using Excel program and SPSS version 21 program. Partial hypothesis testing is used to test the effect of each independent variable used and simultaneous significant test f statistics used to see the presence or absence of the influence of the level of knowledge and awareness simultaneously on the decision to purchase Mango brand women's clothing products. Based on the results of the research the authors did show that product quality has a positive effect on the decision to purchase Mango brand women's clothing products. This can be seen from the t-count value t table and the significance value significance level.